Structural applications of CODE_BRIGHT: a review on numerical modelling of reinforced soil structures - Moncada, Aníbal; Damians, Ivan P. (Frontiers in Built Environment, 2025)
The present document presents a review on the use of the finite element software package CODE_BRIGHT to simulate reinforced soil structures (RSS). RSS are composed of longitudinal steel or polymeric materials, placed orthogonal to the main stress direction in a soil mass, acting as tension-bearing elements. A common application of RSS is in retaining structures, in the form of reinforced soil walls (RSWs). RSW are usually designed with analytical methods, which have limited capabilities when predicting a structure’s deformation response. To improve on this, the use of numerical tools allows to quantify the stress-strain response of complex, compound structures, such as RSWs. Several factors must be considered when modelling RSS, including reinforcement response, which can be non-linear under several circumstance (including time- and temperature-dependencies), soil-reinforcement interaction, soil-structure interaction, and soil response, all of which can be affected by the presence of moisture. Using laboratory measured data, the individual response of reinforcements (e.g., creep elongation), as well as the compound behaviour of soil-reinforcement material (e.g., pullout response) can be simulated to explore individual and compound response. Depending on the modelled phenomena, numerical simulations may include 2D and 3D representations. For full-scale reinforced soil walls, the stress-strain response within the soil mass, reinforcements, concrete facing panels, and connections can be studied in magnitude and distribution. Details regarding special considerations of how to model such structures with CODE_BRIGHT and other commercially available software are provided. Insights on the thermo-hydraulic repone of RSWs are covered. Advantages, limitations and future lines of research in the use of CODE_BRIGHT are explored.